Intentionality or consciousness? - Leclerc, André (2015)
I discuss mainly three points in Fisette’s target paper: 1) Is it true that con- sciousness is as fundamental – or even more fundamental – as intentionality is in Brentano’s philosophy of mind? I shall try to show that intentionality comes first and sheds light on consciousness in Brentano’s work of 1874; 2) I question the idea of self-consciousness as something intrinsic to a mental agent and irreducible to intentionality; 3) finally, is it possible to read Brentano as an intentionalist? I think it is, even if many intentionalists today would not accept Brentano’s whole conception of the mind.